Activity pattern of Cuniculus paca (Rodentia: Cuniculidae) in relation to lunar illumination and other abiotic variables in the southern Brazilian Amazon - Michalski,Fernanda (2011)
Understanding what influences the activity of organisms is important for both ecological understanding and species conservation. Using data from 2,707 camera trap days distributed across 24 forest sites, we present quantitative analyses of the activity pattern of Cuniculus paca (Linnaeus, 1766) in southern Amazonia. We compared the activity pattern of this species across four designated subsets of the 24-hours diel cycle (dawn, dusk, day and night). Using linear regression models we tested the influence of season, temperature and rainfall on the activity patterns of C. paca (paca). We also evaluated the nocturnal photos of paca (N = 111) as a function of the degree of lunar illumination in order to test the prediction that pacas minimize their activity during moon phase when illumination is brighter. Pacas were not recorded during the day but were active at dawn, dusk and night time. We found differences in the influence of the abiotic variables on the nocturnal activity of pacas in the study area. There was no significant difference between the observed (expressed as the frequency of total counts of independent photos over the five classes of lunar illumination) and the expected activity of pacas, based on the frequency of days in the lunar cycle with different classes of lunar illumination, whereas lunar illumination had a weak negative influence on the timing of paca activity (i.e. pacas were active closer to sunset with increasing lunar illumination). However, the timing of nocturnal activity in pacas was not influenced by season, temperature or rainfall. Our findings highlight the ecological plasticity of this Neotropical rodent which has a key function in the maintenance of Neotropical forests.